2016
DOI: 10.5115/acb.2016.49.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of axonal sprouting along rostro-caudal axis of dorsal hippocampus and no neuronal survival in parahippocampal cortices by long-term post-lesion melatonin administration in lithium-pilocarpine model of temporal lobe epilepsy

Abstract: Feature outcome of hippocampus and extra-hippocampal cortices was evaluated in melatonin treated lithium-pilocarpine epileptic rats during early and chronic phases of temporal lobe epilepsy (TLE). After status epilepticus (SE) induction, 5 and 20 mg/kg melatonin were administered for 14 days or 60 days. All animals were killed 60 days post SE induction and the histological features of the rosrto-caudal axis of the dorsal hippocampus, piriform and entorhinal cortices were evaluated utilizing Nissl, Timm, and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(92 reference statements)
0
4
0
1
Order By: Relevance
“…In the pilocarpine-induced SE model, animals treated with melatonin just before, during or after SE, exhibited an increased latency to SE, a survival rate of 100% after SE, a decreased number of seizures in the chronic period and hippocampal neuronal preservation [ 520 ]. Moreover, long-term melatonin administration after SE, reduced neuronal loss showing a region-specific pattern of neuronal protection along the rostro-caudal axis of the dorsal hippocampus [ 521 ]. These results confirm an important role for melatonin in the epileptogenic process as well as the control of seizures.…”
Section: Melatonin and Melatonin-receptorsmentioning
confidence: 99%
“…In the pilocarpine-induced SE model, animals treated with melatonin just before, during or after SE, exhibited an increased latency to SE, a survival rate of 100% after SE, a decreased number of seizures in the chronic period and hippocampal neuronal preservation [ 520 ]. Moreover, long-term melatonin administration after SE, reduced neuronal loss showing a region-specific pattern of neuronal protection along the rostro-caudal axis of the dorsal hippocampus [ 521 ]. These results confirm an important role for melatonin in the epileptogenic process as well as the control of seizures.…”
Section: Melatonin and Melatonin-receptorsmentioning
confidence: 99%
“…Dynamic changes in spectral power of pHFOs in CA1 and CA3 were the most significant. Previous studies have shown that models of TLE are characterized by extensive neuronal loss, reactive gliosis, mossy fiber sprouting, granule cell dispersion, and synaptic remodeling in CA1 and CA3 (36, 37), which are the vulnerable regions after SE (38). It is assumed that these pathological changes lead to the genesis of new hyperexcitable circuits that generate SRS, characterizing the chronic phase.…”
Section: Discussionmentioning
confidence: 99%
“…We used a TLE induction method reported in our previous studies (Kazemi, Shokri, Ganjkhani, Ali, & Iraj, ). Briefly, rats received intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%